2018
DOI: 10.15713/ins.jcri.231
|View full text |Cite
|
Sign up to set email alerts
|

Detection of red complex organisms in chronic periodontitis by multiplex polymerase chain reaction

Abstract: Background: Periodontitis is widely regarded as the second most common disease worldwide after dental decay. The trigger for the initiation of the disease is the presence of complex microbial biofilm in the subgingival area. The Gram-negative anaerobic bacteria have been found to predominate in the subgingival niche. The red complex, which includes Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia encompasses the most important pathogens in chronic periodontitis. The data of these microor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This is mainly due to interspecies interaction, co-aggregation, and metabolic interdependency among these three bacterial species. [6]…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to interspecies interaction, co-aggregation, and metabolic interdependency among these three bacterial species. [6]…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Sanghavi et al (2014) observed the highest detection of P. gingivalis and T. denticola pair in patients with periodontal tissue abscesses. The interaction among these three red complex species is primarily due to their metabolic dependence to each other for survival (Nayak et al, 2018). Having 9 gingivitis individuals with no detection of any red complex species may be due to the fact that red complex bacteria are known to be late colonizers and are more prone to be detected in the advanced stage of periodontitis (Mohanty et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among the classified complexes, the bacterial species from purple, yellow and green complexes are linked to periodontal health, meanwhile the orange, red complex and unclassified species are counted as periodontal pathogens (Popova et al, 2013). The red complex consists of three-member species that are known as keystone pathogens in the development of periodontal disease, namely, Porphyromonas gingivalis, Tannerella forsythia (previously named Bacteroides forsythus, or Tannerella forsythensis) and Treponema denticola (Nayak et al, 2018). Being late colonizers in biofilm community, these bacteria are densely found at periodontitis affected areas (Mohanty et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is recognized as the second most common infection globally after dental deterioration. It is elicited by the formation of a complex biofilm of microbes in the subgingival region, which attach to host cells and tissues, leading to continuous injury and destruction of the tooth-supporting apparatus [ 1 , 2 , 3 ]. The species of bacteria belonging to two major complexes (orange and red complexes) are thought to be etiologic agents of periodontal diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The species of bacteria belonging to two major complexes (orange and red complexes) are thought to be etiologic agents of periodontal diseases [ 4 ]. The red complex bacteria, which consists of Treponema denticola (T. denticola) , Tannerella forsythia (T. forsythia), and Porphyromonas gingivalis (P. gingivalis), is the most significant complex existing together in the subgingival plaque next to the periodontal pocket epithelial lining in deep areas and plays a major collaborative role in the progression of periodontal disease [ 1 ]. Animal researches have also reported the coordinated and collaborative pathogenicity of combined infections with Fusobacterium nucleatum (F. nucleatum) , T. denticola , T. forsythia and Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans), and P. gingivalis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%